Sistem Monitoring Kecepatan Angin Dan Suhu Udara Berbasis Notifikasi Telegram - Deosa Putra Caniago; Rifa’atul Mahmudah Burhan; Refli Noviardi; Muhammad Abrar (AI Society & STMIK Indonesia, 2024)
The unpredictable weather in Batam City impacts the use of sea transportation, which is frequently used by residents for inter-island crossings. There is a need for a real-time monitoring system for wind speed and air temperature, along with notifications when wind speeds become potentially dangerous for sea transportation users. In this research, an Internet of Things (IoT)-based monitoring system for wind speed and air temperature was implemented using the Thingspeak platform for real-time monitoring. The test results demonstrated that the monitoring system could successfully store wind speed and air temperature data in the Thingspeak database. Additionally, Thingspeak was able to display graphs of wind speed and air temperature. The notification tests via Telegram showed that when the wind speed reached 1.5-2.9 m/s, an alert warning was sent, and when the wind speed exceeded 3 m/s, a danger warning was issued.